Service Quality In Increasing Participation Of Co-Operative Members - Yunita Silintowe; Yusepaldo Pasharibu (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2020)
Member participation is a significant element in spurring activity and for maintaining a unifying bond in a co-operative. This study explores service quality's effect on member participation in the primary employee co-operative (primkopkar) Manunggal. This type of research is explanatory with a quantitative approach. The population in this study were members of the Manunggal co-operative, and the sample in this study was 98 people. The data analysis tool used Structural Equation Modeling (SEM), which was processed with the Linear Structural Relationship (LISREL) statistical program. The results showed that service quality had a significant effect on increasing the participation of co-operative members.